Laparoscopic VVF Repair: Current Trends - Mahfouz, Wally; M. Abdel-Karim, Aly (Current Women's Health Reviews, 2013)
Introduction and Objectives: Vesicovaginal fistula (VVF) is the most common type of the genitourinary fistulae. The etiology in the developed countries is commonly following abdominal hysterectomy. In the underdeveloped countries, the etiology is prolonged complicated labor. The best approach for repair; whether abdominal or vaginal; is still debatable. Most experts agree that the optimal technique of repair depends on the surgeon’s familiarity with the approach performed. In the era of minimally invasive surgery, laparoscopy and robotic-assisted laparoscopy have gained popularity in the management of VVF; aiming to decreased morbidity, while preserving the same success rates of the conventional approaches. In this review, we address the role of these minimally invasive surgeries in the management of the VVF, with emphasis on the recent literature review. Materials and Methods: Literature search was done using Medline database with key words: vesicovaginal fistula, laparoendoscopic single site surgery, laparoscopy and robotic repair. Papers written in languages other than English were excluded from our review article. Results: Although many articles have reported laparoscopic repair of VVF, however most of them are case reports and there are only 6 articles that included more than 10 patients. Robotic assisted laparoscopic repair has been reported by 6 different centers, while LESS repair of VVF has been recently reported. Overall success rate was high and comparable with open repair. Most of reports use the classical O’Connor technique. The operative time was quite variable and overall the hospital stay was short. Conclusion: In experienced hands, both traditional and minimally invasive approaches have the same clinical equivalence. The laparoscopic approach requires laparoscopic experience. The daVinci system provides a three-dimensional magnified view, which provides better identification of the surgical planes. LESS repair is feasible too, but requires advanced laparoscopic experience due to the loss of triangulation, which makes it difficult for the free movement of the instruments.
Keywords: minimally invasive